Pembangunan aplikasi permainan strategi untuk latihan penyelesaian masalah (snake defense) - Salim, Muhammad Fadzley (2013)
Learning to sharpen creative and critical thinking was not foreign students in the national education system. In line with the National Education Policy, improving overall quality of education by providing comprehensive education, balanced and integrated. Some transformation in the way of learning in national schools as examples of using computer-aided learning for displaying photos and graphics on science in the classroom. Teaching aids are not limited to just display but with a Computer Assisted Instruction (CAI) methods of learning in school can be enhanced parallel current growing technology. Smartphones and tablet phenomenon is sweeping our country Malaysia. Gadgets, especially smartphones become a trend for people in Malaysia to have. Smartphones have a variety of applications that can help users from various angles such as socializing, playing games, learning and others. Game is the main attraction of smartphone users and is especially worrying half the parents of those kids playing the smart phone. Edutainment industry (Education and Entertaintment) is no longer a foreign in our country. Snake Defense game is a product that provides entertainment and learning in game. This application can improve the skills of analysis, problem solving and making rational decisions. CAI concept and game trends are applied in this application.